How do online users perceive health risks during public health emergencies? Empirical evidence from China - Huang, Shijing; Zhou, Cheng; Yuan, Qinjian; Chen, Guohua; Shen, Hongzhou (Frontiers in Psychology, 2023)
Background The global COVID-19 pandemic has posed a major threat to human life and health, and new media technologies have intensified the spread of risk perception. Purpose This study aimed to explore the impact of risk information ground on online users’ perceived health risks, and further explore the mediating role of psychological distance and the moderating role of self-efficacy. Methods A total of 25 Internet users from different provinces in China were interviewed in-depth, NVIVO.11 was used to qualitatively analyze the interview text data and construct a theoretical model. A total of 492 interviewees were recruited in order to complete a scenario questionnaire, SPSS-27 was used to perform orthogonal experiments, generate eight combinatorial scenarios, analyze demographic data, and clean and prepare data for testing hypotheses. SmartPLS 3.0 was used to test the conceptual model using the structural equation model (SEM) of the partial least squares (PLS). Results The analysis of the SEM model shows that all planned hypotheses (Information fluency → Information diagnosability, Information extensibility → Information diagnosability, Information diagnosability → Psychological distance, Platform interactivity → Scenario embeddedness, Network connectivity → Scenario embeddedness, Scenario embeddedness → Psychological distance, Psychological distance → Risk perception, Psychological distance → Self-efficacy → Risk perception, Information fluency → Information diagnosability → Psychological distance → Risk perception, Information extensibility → Information diagnosability → Psychological distance → Risk perception, Platform interactivity → Scenario embeddedness → Psychological distance → Risk perception, Network connectivity → Scenario embeddedness → Psychological distance → Risk perception) are confirmed. Conclusion This study found that the information ground factors significantly affect online users’ perceptions of health risks, psychological distance mediates the effect of information ground factors on risk perception, and self-efficacy negatively moderates the effect of psychological distance on risk perception.